2014
DOI: 10.1179/1743294413y.0000000198
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of SnBi coatings based on deep eutectic solvent

Abstract: Tin-bismuth (SnBi) alloy coatings were satisfactorily electrodeposited on copper electrodes from a choline chloride-ethylene glycol deep eutectic solvent containing BiCl 3 , ZnCl 2 and H 3 BO 3 . The electrochemical feature of the electrolyte system was inspected via linear sweep voltammetry. The results indicated that the SnBi alloy coating was codeposited as the deposition potential was prolonged up to the potential range, leading to the inadequate deposition of zinc on the copper electrode. Dendrite formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The speciation of Bi III in these DESs is unclear. Recently, the electrodeposition of Sn–Bi coatings on Cu from a DES comprising a 1:2 molar ratio of choline chloride/ethylene glycol (12CE) containing 0.05 m SnCl 2 , 0.05 m BiCl 3 , and 0.1 m H 3 BO 4 as an additive was also reported, but the study focused more on the characterization of the resulting deposits than on the vaguely described electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The speciation of Bi III in these DESs is unclear. Recently, the electrodeposition of Sn–Bi coatings on Cu from a DES comprising a 1:2 molar ratio of choline chloride/ethylene glycol (12CE) containing 0.05 m SnCl 2 , 0.05 m BiCl 3 , and 0.1 m H 3 BO 4 as an additive was also reported, but the study focused more on the characterization of the resulting deposits than on the vaguely described electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Moreover,the electrodeposition of films of BiTeSe from choline chloride DESs with ethylene glycol, malonic acid, or oxalic acid [35] and the electrodeposition of films of BiSe from choline chloride/malonic acid [36] was demonstrated. Thes peciation of Bi III in these DESs is unclear.R ecently,t he electrodeposition of Sn-Bi coatingso nC uf rom aD ES comprising a1 :2 molar ratio of choline chloride/ethylene glycol (12CE) containing 0.05 m SnCl 2 ,0 .05 m BiCl 3 ,a nd 0.1 m H 3 BO 4 as an additive was also reported, [37] but the study focusedm ore on the characterization of the resulting depositst han on the vaguely described electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few investigations related to the electrodeposition of binary and ternary Sn and/or In alloys from DESs have been reported. Gao et al [31] studied the electrodeposition of Sn-Bi alloy from a choline chloride-ethylene glycol deep eutectic solvent. The results suggested the possibility of electroplating the Sn-Bi alloys with their composition around the eutectic point.…”
Section: Introductionmentioning
confidence: 99%
“…A number of the literatures appear in scientific journals connected to the codeposition of SiC, ZrO 2 , Al 2 O 3 , TiO 2 and PTFE with single metal and alloy electrodeposition. [5][6][7][8][9][10][11][12] In 1985, microbiocidal effect of TiO 2 photocatalytic reactions was the first time reported by Matsunaga et al 13 The microbiocidal mechanisms of TiO 2 photocatalysts have been investigated in detail. 14,15 Kikuchi and coworkers showed that TiO 2 films coated on different substrates such as glass, tiles and stainless steel possessed antibacterial functions under weak ultraviolet light in living areas, and the viable number of Escherichia coli significantly decreased on the illuminated TiO 2 film.…”
Section: Introductionmentioning
confidence: 99%